Alzheimer's disease public‐private partnerships: Update 2014. Issue 6 (13th September 2014) - Snyder, Heather M.; Kim, Hye; Bain, Lisa J.; Egge, Robert; Carrillo, Maria C.
Abstract: The National Plan to Address Alzheimer's Disease highlights the need for coordinated public‐private partnerships. In recent years, the number of collaborations and consortia have expanded and grown in Alzheimer's research. The Alzheimer's Association compiles this annually updated compendium to centralize this inventory of partnerships in an effort to synergize these activities. This manuscript reflects the 2014 landscape of non‐profit organizations who engage in public‐private partnerships to promote and support dementia research.